Prophylaxis of Post Spinal Shivering: A Comparative Study between Intravenous Ondansetron and Meperidine - Begum, Shamim Ara; Hasan, Sanjida; Banik, Chandan Kumar; Begum, Yasmin Ara; Sultana, Mosammat Rehana; Chowdhury, Gulshan Ara (Journal of Chittagong Medical College Teachers’ Association, 2021)
Background: Shiveringis a common complication following anesthesia. Many drugs have been documented as a prophylaxis of postanesthesia shivering. The aim of this study was to find out a better drug as an antishivering agent. Materials and methods: This comparative study was carried out in the Department of Anesthesiology in Chittagong Medical College Hospital over a period of 6 months starting from November 2015 to April 2016. A total 90 obstetric patients with American Society of Anesthesiology (ASA) physical status I & II underwent cesarean section received placebo (Group-C, n-30), Inj-Ondansetron 8mg (Group-O, n-30) and Inj-Meperidine 0.4mg/kg (Group-M, n-30). These drugs were administered during intraoperative period just after cord clamp. Incidence of shivering, hemodynamic parameters were observed immediate after spinal anesthesia & then 5 min interval for 30 min throughout the intraoperative period. Results: Shivering was observed in 16 patients (53.33%) of group-C, 4 patients (13.33%) of group O and 8 patients (26.66%) of group M. The number of patient with a shivering grade 3 & 4 were very highly significant (p<0.001) in group C compared with other groups at 15 min & 20 min after block & significant (p<0.05) at 25 min & 30 min after block. Conclusion: Ondansetron was found to be more effective and haemodynamically stable drug than Meperidine in prophylaxis of post spinal shivering. JCMCTA 2021 ; 32 (1) : 53-58